Specialisations of University Graduates and Changes in the Labour Market in Wielkopolska - Mrozińska , Agnieszka (Studia Oeconomica Posnaniensia, 2017)
Creating a knowledge-based economy and cooperation in the conditions of globalization and economic integration has led to changes in the labour market; this has led to changes in the situation in higher education in Poland. Adapting the offer of Polish universities to the demands of employers is an expression of the implementation of the educational aspirations of future employees. The aim of the paper is to compare the processes of the change taking place in the specialisation’s structure of study at universities with changes taking place in the labour market in Poznań and Great Poland. The research indicates the changes that have occurred in the structure of graduates’s specialisations and in the structure of the labour market, and then focuses on the analysis of the intensity, speed and monotonicyty of the process of the adaptation of these structures in 2008-2014.